Bishop Lamont and Hermeneutics of Play Hip Hop, Religion, and the Study of American Religious History - Rolsky, L. Benjamin (2011)
This paper investigates the subject of hip-hop within the study of religion and the study of American religion and culture. In particular, the paper focuses on the corpus of California hip-hop artist Bishop Lamont in developing a "hermeneutics of play" through a combinative "lived religion" approach as a way of reading and reflecting on the larger religious significance of hip-hop in late 20th century America. As both a reading practice and a subject of study for both historians and religious studies scholars, hip-hop comes into view in this paper as an essential component in narrating an American religious history of the last three decades. Hip-hop and its study also reveals its own understandings of religion, America, and American religion as articulated through post-industrial and a variety of religious vocabularies that have been largely ignored by scholars of religion. In essence, this paper argues that by exploring the rhetorical, religious, and existential complexity found within hip-hop cultures, a more complex post-1965 American religious landscape emerges for both the historian and theorist of religion.
Keywords: American Religious History; Hip-hop; Rap; theory of religion